High Pretreatment Platelet-to-Albumin Ratio Predicts Poor Survival Results in Locally Advanced Nasopharyngeal Cancers Treated with Chemoradiotherapy - Haksoyler V; Topkan E (Dove Medical Press, 2021)
Veysel Haksoyler,1 Erkan Topkan2 1Medline Hospital, Department of Medical Oncology, Adana, Turkey; 2Baskent University Medical Faculty, Department of Radiation Oncology, Adana, TurkeyCorrespondence: Erkan TopkanBaskent University Medical Faculty, Department of Radiation Oncology, Adana, 01120, TurkeyTel +90-533-7381069Fax +90-322-3444452Email docdretopkan@gmail.comPurpose: In a lack of similar research, we assessed the prognostic utility of pretreatment platelet-to-albumin ratio (PAR) in locally advanced nasopharyngeal carcinoma (LANPC) patients managed with concurrent chemoradiotherapy (CCRT).Patients and Methods: Present retrospective analysis included a sum of 128 consecutively treated LANPC patients who underwent cisplatinum-based radical CCRT. Availability of an ideal pretreatment PAR cutoff that may stratify the study population into two cohorts with significantly distinct survival outcomes was sought by utilizing the receiver operating characteristic (ROC) curve analysis. The primary and secondary endpoints were overall survival (OS) and progression-free survival (PFS), respectively.Results: A rounded 5.2 [area under the curve (AUC): 68.9%; sensitivity: 67.4%; and specificity: 65.2%] value was identified as the ideal PAR cutoff that grouped patients into two gatherings [PAR≥ 5.2 (N=60) versus < 5.2 (N=68)]. The median follow-up duration was 86.4 months (range: 9- 147). Kaplan-Meier comparisons between the two PAR groups revealed significantly diminished median PFS (69.4 versus 106.8 months for PAR< 5.2; P< 0.012) and OS (88.3 versus not reached yet for PAR< 5.2; P= 0.023) for the PAR ≥ 5.2 group. The results of multivariate analyses affirmed the pretreatment PAR≥ 5.2 as an independent prognostic factor that indicates diminished PFS (P= 0.016) and OS (P= 0.019) together with the respective N2-3 nodal stage (versus N0-1; P< 0.05 for PFS and OS, respectively) and weight loss > 5% at past six months (≤ 5%; P< 0.05 for PFS and OS, respectively).Conclusion: The results of the current retrospective analysis provided a robust and independent adverse prognostic value for pretreatment PAR ≥ 5.2 in terms of median and long-term PFS and OS outcomes in LA-NPC patients this patient group treated with conclusive CCRT.Keywords: concurrent chemoradiotherapy nasopharyngeal cancer, platelet-to-albumin ratio, prognostic worth, survival results